Blood Glucose Levels - Szablewski, Leszek (IntechOpen, 2020)
The main source of energy for the body is glucose. Its low blood concentrations can cause seizures, loss of consciousness and death. Long lasting high glucose levels can cause blindness, renal failure, cardiac and peripheral vascular disease, and neuropathy. Blood glucose concentrations need to be maintained within narrow limits. The process of maintaining blood glucose at a steady state is called glucose homeostasis. This is achieved through a balance of the rate of consumption of dietary carbohydrates, utilization of glucose by peripheral tissues, and the loss of glucose through the kidney tubule. The liver and kidney also play a role in glucose homeostasis. This book aims to provide an overview of blood glucose levels in health and diseases.